Dampak Sektor Transportasi Terhadap Perekonomian di Timor Barat: Suatu Analisis Model Input - Output (I-O) - Thobias Arnoldus Messakh; Ernan Rustiadi; Eka Intan Kumala Putri; Akhmad Fauzi (Jurnal Wilayah dan Lingkungan, 2021)
The development of the transportation sector on the West Timor is expected to be a driving machine in supporting other sectors, so that it will have a large multipler impact on the economy at the land borders of the country with Timor Leste. The government needs to make breakthroughs in the development of the transportation sector, because West Timor is experiencing a transportation infrastructure deficit. This is due to the low quality and quantity of transportation infrastructure capable of supporting the regional economy. This study aims to examine the impact backward and forward, as well as the multiplier impact of development on West Timor in 2018. The result of the researched was that the transportation sector in West Timor has a degree of distribution of 1.40. While the degree of sensitivity was 0.486. The multiplier effect on salaries and wages (multiplier income) is 2.069, and the impact on the total value added multiplier is 1.409. The transportation sector needs to be maximized by building intermoda connectivity of the transportation network that is more effective and efficient. It is also necessary to optimize connectivity in integrating the development phases of National, Provincial and District road sections. The network connectivity is expected to be able to encourage the production sector which is able to increase or develop production capacity, thus providing a more optimal multiplier impact in the future.